System identification of Meridian unmanned aerial system - Keshmiri, Shawn; Ewing, Mark; Hale, Richard (Kansas State University, 2013)
The unsteady and nonlinear aerodynamic characteristics of the Meridian unmanned aerial system in the presence of wind shear are investigated using the recorded test data during flights in Polar Regions. The main purpose of this paper is to determine the reasons for and characteristics of oscillations that occurred in the flight for improvement of autopilot design and ground operator training.
Keywords: Unmanned air vehicles; Fuzzy logic modeling; Aerodynamics